Design and applications of highly dispersive photonic crystal fibers - Zhang, Peng Fei (2010)
Photonic crystal fiber (PCF) has been studied extensively these years. An important use of PCF is dispersion compensation. Previous dispersion compensation PCF cannot achieve high dispersion values and large bandwidth simultaneously. Recently, broadband highly dispersive PCFs (HD-PCF) including Hexagonal PCF (H-PCF) and Octagonal PCF (O-PCF) are introduced. This project aims to design a HD-PCF with absolute dispersion value larger than 200 ps/km/nm and dispersion fluctuation smaller than 5% over C-band. Systematic study on the influence of structural variations on the dispersion property of HD-PCF is carried out through the project. Various designs are proposed and studied. By using the optimized design parameters, the dispersion is -400 ps/km/nm when the wavelength is 1.55 μm.